Dancing the Waterways in Leanne Simpson’s she sang them home - Mumford, Cara (Performance Matters, 2021)
Inspired by essay films meditating on time, travel and ceremony and informed by cinematic cartography, my short dance film, sing them home (2020), travels the specific bodies of water that form the route that Atlantic Salmon once journeyed as they migrated to Michi Saagiig Nishnaabeg territory. Rooted in Nishnaabewin and Indigenous food sovereignty, toward a vision of the collective continuance of Michi Saagiig aki miijim, the film uses movement to activate sites in and on the shores of these lakes and rivers in the present while remembering the past and future of this waterway and her kin. This photo essay documents the film's journey and invites you to consider the making of this dance film as a prayer for the salmon to return.